Circular RNAs as New Regulators in Gastric Cancer: Diagnosis and Cancer Therapy - Wu, Wei; Zhen, Tianyuan; Yu, Junmin; Yang, Qingli (Frontiers in Oncology, 2020)
Gastric cancer (GC) is one of the most diagnosed cancers that causes high mortality in the world. Although the surgery tools and chemotherapies have significantly improved the overall survival of patients with GC, the early diagnosis of GC remain insufficient and many patients diagnosed with advanced stages of GC however were not able to be benefited from curative therapy. Circular RNAs (circRNAs), novel members of the noncoding cancer genome, are being explored involving in various cancer types including in GC. CircRNAs could work as miRNA sponges to regulate cell proliferation, cell migration, and cell cycle in GC. In addition, it was found that abnormal expression of circRNAs was associated with pathological characteristics in GC tissues, which could help to act as potential markers of early diagnosis or predictors of prognosis. Although various functional circRNAs have been discovered and characterized, the studies of circRNAs in GC are still at the beginning compared with other RNAs. In order to provide a whole view to better understand the circRNAs in the occurrence and development of GC, we review the current knowledge on circRNAs in relation to their expression and regulation in GC as well as their potential to be diagnosis markers and their role in drug resistance will be mentioned. It is helpful to address their possibility from basic research into practical application.